A unifying concept of animal breeding programmes. (24th January 2021) - Simianer, Henner; Büttgen, Lisa; Ganesan, Amudha; Ha, Ngoc Thuy; Pook, Torsten
Abstract: Modern animal breeding programmes are constantly evolving with advances in breeding theory, biotechnology and genetics. Surprisingly, there seems to be no generally accepted succinct definition of what exactly a breeding programme is, neither is there a unified language to describe breeding programmes in a comprehensive, unambiguous and reproducible way. In this work, we try to fill this gap by suggesting a general definition of breeding programmes that also pertains to cases where genetic progress is not achieved through selection, but, for example, through transgenic technologies, or the aim is not to generate genetic progress, but, for example, to maintain genetic diversity. The key idea of the underlying concept is to represent a breeding programme in modular form as a directed graph that is composed of nodes and edges, where nodes represent cohorts of breeding units, usually individuals, and edges represent breeding activities, like "selection" or "reproduction." We claim, that by defining a comprehensive set of nodes and edges, it is possible to represent any breeding programme of arbitrary complexity by such a graph, which thus comprises a full description of the breeding programme. This concept is implemented in a web‐based tool (MoBPSweb, available at www.mobps.de ) and has a link to the R‐package MoBPS (Modular Breeding Program Simulator) to simulate the described breeding programmes. The approach is illustrated by showcasing three different breeding programmes of increasing complexity. The concept allows a formal description of breeding programmes, which is requested, for example, in legal regulations of the European Union, but so far cannot be provided in a standardized format. In the discussion, we point out potential limitations of the concept and argue that the general approach can be easily extended to account for novel breeding technologies, to breeding of crops or experimental species, but also to modelling diversity dynamics in natural populations.